2020
DOI: 10.1021/acsami.0c17496
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Absorber Layer Morphology on Photovoltaic Properties in Solution-Processed Chalcopyrite Solar Cells

Abstract: Solution-processed chalcopyrite solar cells can be economically produced on a large scale; however, for them to be commercially viable, their low efficiency and detrimental processing have to be overcome. To this end, extensive research efforts have been devoted to boost device efficiency and develop benign solution processes. In this review, relevant processes are categorized into molecular-based and particulate-based solution processes, and progress is evaluated in terms of device performance and processing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 70 publications
(182 reference statements)
0
7
0
Order By: Relevance
“…Hence, the inferior material quality of the solution process prepared CIGS absorber is responsible for the poor device performance. [11,12] Typically, the solution-processed CIGS thin films exhibit small grains, whereas the vacuum-processed CIGS films present large grains. [13,14] Meanwhile, more defects may exist in the solution-processed CIGS films because of the residual solvent impurities and impurities introduced during film preparation.…”
mentioning
confidence: 99%
“…Hence, the inferior material quality of the solution process prepared CIGS absorber is responsible for the poor device performance. [11,12] Typically, the solution-processed CIGS thin films exhibit small grains, whereas the vacuum-processed CIGS films present large grains. [13,14] Meanwhile, more defects may exist in the solution-processed CIGS films because of the residual solvent impurities and impurities introduced during film preparation.…”
mentioning
confidence: 99%
“…Based on the published papers, the correlation between the average grain size of solution‐processed CIGS solar cells and photovoltaic characteristics was obtained. [ 25 ] From the results, J sc increased with average grain size and saturated with further increase in the grain size (Figure 20d). V oc,def decreased with increasing average grain size and power conversion efficiency (PCE) increased with the grain size (Figure 20e,f).…”
Section: Outlook: Lesson From Correlations Between Materials and Elec...mentioning
confidence: 93%
“…We previously demonstrated that J sc increases and V oc,def decreases as the grain size increases in solution‐processed CIGS solar cells by analyzing previously reported results. [ 25 ] This indicates that it is important to fabricate high‐quality large‐grained CIGS thin films with few crystal defects prior to controlling the other electrical properties. Because Se vapor is primarily used for selenization in solution‐processed CIGS, processes that produce large grains are required.…”
Section: Outlook: Lesson From Correlations Between Materials and Elec...mentioning
confidence: 99%
See 2 more Smart Citations